Hubungan Tingkat Pengetahuan Ibu dan Usia terhadap Penggunaan Alat Kontrasepsi Suntik - Lia Hartini; Omi Harera Prabusari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the factors associated with the use of injection contraceptives in mothers visiting the Swasti Saba Public Health Center in Lubuklinggau City in 2019. This research method uses descriptive analytic with a cross sectional approach. These results obtained respondents with good knowledge (43.3%), lack of knowledge (56.8%), young age (64.9%), old age (35.1%), use of injectable contraceptives (51.4%) and the use of non-injectable contraceptives (48.6%). Chi square statistical test results obtained value ρ> α (0.05) for knowledge of p = 0.129 and age with a value of p = 0.418. In conclusion, there is no significant relationship between knowledge and age with injection contraceptive use. Keywords: Injection Contraception, Knowledge, Age